Deletion of Dicer blocks osteogenic differentiation via the inhibition of Wnt signalling - Wu, Hong‑Yan; Bi, Rui; Sun, Ting; Xie, Fei (Molecular medicine reports, 2019)
Micro (mi)RNAs are small, non‑coding RNAs and have been reported to have important roles in the epigenetic control of bone development. miRNAs markedly regulate osteoblast differentiation through stages of maturation as well as the activities of osteogenic signaling pathways. Dicer is an important endoribonuclease that regulates miRNA maturation. Previous studies have demonstrated that Dicer deletion decreases fetal survival and bone formation, while excision in differentiated osteoblasts increases bone mass. However, the underlying molecular mechanisms remain unclear. In the present study, whether the deletion of Dicer affects Wnt signaling, which exhibits important roles during osteogenesis, was investigated. Bone marrow stromal cells (BMSCs) were used as an osteogenic model. Dynamic changes of seven Wnt genes and downstream T‑cell factor 1 (Tcf‑1)/lymphoid enhancing binding factor were observed during the osteogenic differentiation of BMSCs, which revealed different roles at early and late differentiation stages. Following the stable knockdown of Dicer in BMSCs using lentiviral short hairpin RNA, osteogenic differentiation was blocked, and the levels of important osteogenic differentiation markers (runt related transcription factor 2 and alkaline phosphatase) were markedly inhibited. Furthermore, stage specific regulation of Wnt genes in Dicer‑deficient BMSCs was investigated in the present study. At the early differentiation stage (days 5‑7), knockdown of Dicer led to the inhibition of Wnt1, Wnt7 and Wnt10b, as well as the upregulation of Wnt4, Wnt10a and Tcf‑1. At the late stage of differentiation (days 14‑21), knockdown of Dicer significantly suppressed the expression levels of all of the included Wnt genes as well as Tcf‑1, with the exception of Wnt10a. The upregulation of Wnt10a following the deletion of Dicer was maintained throughout all stages of differentiation. In addition, differential regulation of Wnt genes and Tcf‑1 were revealed to be associated with dynamic changes in their expression levels during osteogenic differentiation. Furthermore, the four putative Wnt10a‑targeting miRNAs were investigated in the present study, and the results demonstrated that they were upregulated during osteogenic differentiation, which suggested that inhibition of Wnt10a may be an important factor associated with osteogenic differentiation. In conclusion, the present study investigated the mechanism underlying the regulation of Wnt signalling by Dicer during osteogenesis, and identified potential miRNAs targeting the components of Wnt signalling influenced by Dicer. Collectively, the present study identified the association between Dicer and Wnt signalling during bone development.